(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The main aim of the project is to save the child from threads. Day by day, the safety measurement of children has been reduced due to the busy schedule of parents. Violence against children has been increasing. This problem arises not only for children but also women’s. By taking the single step forward to save the child. This project is mainly focused on sensing children’s movement and monitoring the child by received signal strength (RSS). Here instead of GPS, we are RSS-received signal strength. Through RSS, the child has been monitored continuously. If a child reaches a critical state, the system notifies the parents of the location. It has a MEMS micro-electromechanical system sensor. The key application of RSS is easy, low-cost. RSS involves a localization process across wireless networks (WSNS). RSS is a more practical indoor localization background. This acts as a wearable device. Now a days most wearable devices are available in the market, and they are used for security purposes. Some of the wearable devices require smart phones to operate, but everyone doesn’t have the ability to maintain the smart phone the device replaced.